2007
DOI: 10.1111/j.1600-6143.2007.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Islets Derived From Donors After Cardiac Death Are Fully Biofunctional

Abstract: Islets from brain-dead donors (BDDs) are being used in the treatment of Type 1 diabetes. However, both donor numbers and islet survival are limited. We explored the clinical potential for islets from non-heartbeating donors (NHBDs), who have lower circulating cytokines, by comparing islets from 10 NHBDs against 12 identically-isolated islets from BDDs over the same time period. The quantity and quality of islets from NHBDs was good. NHBD yielded ∼12.6% more islets than those of BDDs (505 000 ± 84 230 vs. 400 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
2
30
1
Order By: Relevance
“…The tolerance of the pancreas to warm ischaemia is likely to be between these extremes, as animal models have shown decreased islet viability after warm ischaemia of more than 30 min 28 -30 . This finding was reinforced in a study of human islets from 12 DCD donors, in which all isolates were biologically functional when the duration of systolic blood pressure below 50 mmHg was less than 25 min 26 .…”
Section: Discussionmentioning
confidence: 76%
“…The tolerance of the pancreas to warm ischaemia is likely to be between these extremes, as animal models have shown decreased islet viability after warm ischaemia of more than 30 min 28 -30 . This finding was reinforced in a study of human islets from 12 DCD donors, in which all isolates were biologically functional when the duration of systolic blood pressure below 50 mmHg was less than 25 min 26 .…”
Section: Discussionmentioning
confidence: 76%
“…In a clinical setting, Zhao et al . showed that DCD donor organs yielded 12.5% more islets than DBD organs. It should be noted that a proportion of DCD donors probably fulfil the criteria for brain death (but are not tested), so this may be an underestimate of the true effect.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…This issue is especially important because the pancreatic overexpression of iNOS has been related to the apoptosis of acinar cells and acute rejection in animal models (43) and plays an important role in acute and severe hypoxic injury to pancreatic beta cells (44). To date, although solid pancreas transplantation remains challenging, successful islet isolation and transplantation from NHBD have been reported (45,46). Our results indicate that the pancreas from UNHBD shows acceptable tissue damage.…”
Section: Discussionmentioning
confidence: 52%